EARLY PREGNANCY DIAGNOSIS THROUGH TRANSRECTAL ULTRASONOGRAPHY AND PLASMA PROGESTERONE ASSAY IN KANKREJ COWS - BHORANIYA, H L; DHAMI, A J; NAIK00, M; DIVEKAR, B S (The Indian Journal of Animal Reproduction, 2011)
The ultrasound examinatlons were performed on 26 experimentally induced estrus Kankrej cows at day 26 and 40 post-insemination using a real-time B-mode scanner equipped with a 5 MHz linear array transducer. The results were correlated with the findings of plasma progesterone on day 20 and palpation per rectum on day 60 post-insemination with respect to sensitivity, specificity, reliability and accuracy of ultrasound scanning. Ultrasound scanning of uterus on day 26 post-Al revealed the embryo proper in 11 of 12 predicted pregnant cows, though embryonic vesicle was seen in all 12. Moreover, both embryonic vesicle and embryo proper were detected in all 15 predicted pregnant animals on day 40 post-Insemination. The sensitivity of ultrasound scanning for early pregnancy on days 26 and 40 was 85.71 and 93.75 %, and the specificity 75.00 and 100.00 %, respectively. The positive predictive values of early pregnancy were 80.00 and 100.00 % on days 26 and 40, while the negative predictive values were 81 .82 and 90.91 %. The overall diagnostic accuracy of USG was found to be 80.77 and 96.15 % on days 26 and 40 post-Al, respectively, and that for plasma progesterone assay on day 20 post-Al was 86.66 %. The plasma progesterone concentrations on day 20 post-Al were significantly higher in conceived cows as compared to non-conceived cows in all the experimental animals. Thus transrectal USG is a fairly reliable, instant and accurate means of detecting early pregnancy in zebu cows.